Cohabitation among Undergraduates of the University of Benin, Edo State, Nigeria - Obarisiagbon, Emmanuel Imuetinyan (NIU Journal of Social Sciences, 2023)
There has been a steady upsurge in students’ embrace of off-campus accommodation in Nigerian universities. This ordinarily ought not to be an issue but for the fact that the students have turned such off-campus accommodation into cohabitation centres. This study therefore interrogates cohabitation among undergraduates of the University of Benin, Nigeria. The study anchors its theoretical orientation on the norm activation theory. The study was conducted using the descriptive survey method where 650 undergraduates from 63 departments in the university were sampled and administered a self-designed questionnaire. The study found that inadequate provision of hostel facilities by the university management is a motivation for cohabitation by students’ resident in off-campus accommodation and that most of such students end up with unwanted pregnancies and abortion. The study therefore recommends the provision of more hostel facilities by the management of the University of Benin, Nigeria as well as engaging landlords of off-campus accommodation and community leaders in a bid to have them assist in supervising and monitoring off-campus students. Keywords:    Prevalence, cohabitation, university, off-campus, hostel issues, undergraduates